ChemInform Abstract: Indium‐Mediated Stereoselective Allylation. Issue 50 (November 2016) - Kumar, Dinesh; Vemula, Sandeep R.; Balasubramanian, Narayanaganesh; Cook, Gregory R.
Abstract: Review: 55 refs.